Hydrodynamics of Droplet Sorting in Asymmetric Acute Junctions - He Yang; Tuomas P. J. Knowles (Micromachines, 2022)
Droplet sorting is one of the fundamental manipulations of droplet-based microfluidics. Although many sorting methods have already been proposed, there is still a demand to develop new sorting methods for various applications of droplet-based microfluidics. This work presents numerical investigations on droplet sorting with asymmetric acute junctions. It is found that the asymmetric acute junctions could achieve volume-based sorting and velocity-based sorting. The pressure distributions in the asymmetric junctions are discussed to reveal the physical mechanism behind the droplet sorting. The dependence of the droplet sorting on the droplet volume, velocity, and junction angle is explored. The possibility of the employment of the proposed sorting method in most real experiments is also discussed. This work provides a new, simple, and cost-effective passive strategy to separate droplets in microfluidic channels. Moreover, the proposed acute junctions could be used in combination with other sorting methods, which may boost more opportunities to sort droplets.